Implementation of Value Added Tax Rate Increase Based on Harmonization of Tax Regulations - Aprilia, Sinta Ananda Rizqi; Yasir, Muhammad; Labibah, Hanin Alya (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: The implementation of the increase in the Value Added Tax (VAT) rate to 12% based on Law Number 7 of 2021 and its legal implications on the principles of legality and legal certainty in the Indonesian tax system.Purposes of the Research: The objective of this study is to examine the legal basis of governmental authority and to analyze the legal issues arising from the implementation of the 12% Value Added Tax rate increase, particularly in relation to the principles of legality and legal certainty within the Indonesian tax law framework.Methods of the Research: This study employs a normative legal research method using statutory and conceptual approaches. Legal materials are collected through document analysis of statutory regulations and legal literature. The analysis is conducted qualitatively to systematically interpret legal norms, assess their consistency, and evaluate their implications for legal certainty within the Indonesian tax law framework.Results Main Findings of the Research: The findings indicate that the 12% Value Added Tax increase under Law Number 7 of 2021 complies with the principle of legality under Article 23A of the 1945 Constitution. However, its implementation through a Minister of Finance Regulation using an alternative tax base raises legal concerns due to differing effective tax rates, potentially causing legal uncertainty and tax disputes.